2018
DOI: 10.1007/s00382-018-4118-2
|View full text |Cite
|
Sign up to set email alerts
|

The Karakoram/Western Tibetan vortex: seasonal and year-to-year variability

Abstract: The "Karakoram Vortex" (KV), hereafter also referred to as the "Western Tibetan Vortex" (WTV), has recently been recognized as a large-scale atmospheric circulation system related to warmer (cooler) near-surface and mid-lower troposphere temperatures above the Karakoram in the western Tibetan Plateau (TP). It is characterized by a deep, anti-cyclonic (cyclonic) wind anomaly associated with higher (lower) geopotential height in the troposphere, during winter and summer seasons. In this study, we further investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 51 publications
5
38
0
Order By: Relevance
“…By day 0, the cold anomalies had started to invade the atmosphere above the SETP (Figure g). Together with the cyclonic anomaly over the TP on day 0, these cold anomalies are consistent with the “warm high/cold low” temperature‐circulation relationship over the Karakoram‐West TP previously identified by Forsythe et al () and Li et al (). Their findings regarding this temperature–circulation relationship can therefore be applied to nearly the entire TP.…”
Section: Thermodynamic Conditions Necessary For Wintertime Extreme Prsupporting
confidence: 89%
See 1 more Smart Citation
“…By day 0, the cold anomalies had started to invade the atmosphere above the SETP (Figure g). Together with the cyclonic anomaly over the TP on day 0, these cold anomalies are consistent with the “warm high/cold low” temperature‐circulation relationship over the Karakoram‐West TP previously identified by Forsythe et al () and Li et al (). Their findings regarding this temperature–circulation relationship can therefore be applied to nearly the entire TP.…”
Section: Thermodynamic Conditions Necessary For Wintertime Extreme Prsupporting
confidence: 89%
“…By contrast, the vertical advection and the diabatic heating played roles in inhibiting the rapid temperature drop. As pointed out by Forsythe et al (2017) and Li et al (2018), the large cold anomalies associated with the cyclonic anomaly (i.e., the cold low) over the Karakoram-West TP were mainly generated by the adiabatic cooling due to the powerful upward motion. Thus, the heat budget analysis here indicates that their finding about the dominant role of the adiabatic cooling in the formation of cold anomalies in the cyclonic anomaly can be applied to nearly the whole TP region.…”
Section: Heat Budget Analysis Of the Temperature Variationmentioning
confidence: 85%
“…Both orographic and convective uplift favor the occurrence of precipitation over the southern TP (Tucker, ). In addition to these two lifting processes, further study has revealed that cyclonic systems moving along the subtropical westerly jet stream play an important role in triggering wintertime intense precipitation over the TP by strengthening large‐scale moisture convergence and updrafts (Cannon et al, , , ; Dimri et al, ; Forsythe et al, ; Lang & Barros, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the region of correlated near-surface temperatures associated with the WTV also includes regions that experience rapid decline of glaciers, such as Spiti Lahaul (Brun et al, 2017). Precipitation associated with the WTV might shed more light on this issue (Li et al, 2018), but the WTV might not be the main dynamical response to changes in precipitation, as it is for changes in temperature (Acosta & Huber, 2017;Cannon et al, 2015;Cash et al, 2015). Precipitation associated with the WTV might shed more light on this issue (Li et al, 2018), but the WTV might not be the main dynamical response to changes in precipitation, as it is for changes in temperature (Acosta & Huber, 2017;Cannon et al, 2015;Cash et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Another suggestion was put forward by Forsythe et al (2017), who found that temperatures in northwestern HMA highly correlate with the circulation around northwestern HMA at pressures between 500 and 200 hPa. This structure of correlated atmospheric variables was dubbed the "Karakoram Vortex," or "Western Tibetan Vortex" (WTV) by Forsythe et al (2017) and following work by Li et al (2018Li et al ( , 2019, together referred to as FL17-19 here. They propose that adiabatic heating and cooling, caused by the vortex, is the driver of temperature changes in northwestern HMA.…”
Section: Introductionmentioning
confidence: 99%